2010
DOI: 10.1177/1359105309346342
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Sleep Hygiene Practices in Good Sleepers and Patients with Insomnia

Abstract: Previous studies examining the associations between sleep hygiene practices and insomnia have produced inconsistent results. This study further investigates this issue by examining different domains of sleep hygiene separately. One hundred and six insomnia patients and 89 good sleepers participated in the study. Their sleep hygiene, sleep quality and insomnia severity were assessed with subjective rating scales. Among good sleepers, almost all domains of sleep hygiene correlated significantly with their sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 22 publications
(25 reference statements)
8
84
1
5
Order By: Relevance
“…23,48 However, other studies have failed to observe differences in sleep hygiene behaviors between those with and without insomnia. [49][50][51] Interestingly, our data are consistent with the findings of Cheek and colleagues, 24 who found that midlife women with insomnia consumed less caffeine and were more likely to abstain from alcohol compared with women without insomnia. It is possible that midlife women suffering from insomnia are more mindful of the detrimental effects of poor sleep hygiene and, as a result, are more likely to follow positive sleep hygiene behaviors and avoid negative sleep hygiene behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…23,48 However, other studies have failed to observe differences in sleep hygiene behaviors between those with and without insomnia. [49][50][51] Interestingly, our data are consistent with the findings of Cheek and colleagues, 24 who found that midlife women with insomnia consumed less caffeine and were more likely to abstain from alcohol compared with women without insomnia. It is possible that midlife women suffering from insomnia are more mindful of the detrimental effects of poor sleep hygiene and, as a result, are more likely to follow positive sleep hygiene behaviors and avoid negative sleep hygiene behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…When considered in light of clinically significant insomnia prevalence as high as 50% among veterans, 5 and prior research suggesting that only half of patients with probable insomnia discuss their insomnia complaint with their PCP, 18,19 it appears from our findings that veterans report insomnia to their VA PCPs at rates similar to the general population (20% to 39%). In prior research, those discussing their insomnia complaint with their providers had more comorbid conditions and poorer self-ratings of overall health.…”
Section: Discussionmentioning
confidence: 58%
“…In prior research, sleep hygiene was strongly associated with sleep quality among normal sleepers but not in those with insomnia. 18 Findings for PCP documentation of insomnia in the medical record were noteworthy as well. In prior research, Hermes and colleagues 32 suggested that, more often than not, insomnia is not documented in the medical record by VA health care providers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SHPS is a 30-item self-rating scale. Respondents rate how frequently they engage in behavioral practices on a 6-point Likert scale, ranging from 1 (never) to 6 (always) (Yang, Lin, Hsu, & Cheng, 2010). Higher scores indicate a higher frequency of inappropriate sleep hygiene behavior (Lin, Yang, Hsu, & Cheng, 2009).…”
Section: Sleep Hygiene Practice Scalementioning
confidence: 99%